2018
DOI: 10.1002/dvdy.24641
|View full text |Cite
|
Sign up to set email alerts
|

Intercalated cushion cells within the cardiac outflow tract are derived from the myocardial troponin T type 2 (Tnnt2) Cre lineage

Abstract: Intercalated cushions of the developing outflow tract are populated with Tnnt2-Cre derived cells, a Cre reporter previously used for tracing and excision of myocardial cells and not previously associated with mesenchymal cells. Developmental Dynamics 247:1005-1017, 2018. © 2018 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 38 publications
2
45
1
Order By: Relevance
“…In both mammals and birds, but not in crocodilians, a solution for the addition of the third cusp is found by adding an intercalated swelling . All these authors agree on the importance of the SHF but vary in their explanation for the development of bicuspidy by describing either a non‐anlage of intercalated cusps or a non‐disjunction from the main endocardial OFT cushion .…”
Section: Evo‐devo Aspects Of Congenital Malformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In both mammals and birds, but not in crocodilians, a solution for the addition of the third cusp is found by adding an intercalated swelling . All these authors agree on the importance of the SHF but vary in their explanation for the development of bicuspidy by describing either a non‐anlage of intercalated cusps or a non‐disjunction from the main endocardial OFT cushion .…”
Section: Evo‐devo Aspects Of Congenital Malformationsmentioning
confidence: 99%
“…In both mammals and birds, but not in crocodilians, a solution for the addition of the third cusp is found by adding an intercalated swelling. 133,226,227 All these authors agree on the importance of the SHF but vary in their explanation for the development of bicuspidy by describing either a non-anlage of intercalated cusps or a non-disjunction from the main endocardial OFT cushion. 133 The difference in incidence of bicuspidy in the aortic vs the pulmonary orifice might have a hemodynamic background related to the difference in mass addition of SHF cells between the aortic and pulmonary sides (as might be inferred from Scherptong et al 89 ).…”
Section: Bicuspid Semilunar Valvesmentioning
confidence: 99%
“…Endothelial Nos3 plays an important role in aortic valve development, as shown by the presence in Nos3−/− mice of partially penetrant R-N BAVs [16] and a study has presented a significant decrease in Nos3 protein amount in BAV compared to tricuspid aortic valve (TAV) human tissues [17]. More recently, second heart field cells have been proposed to contribute to intercalated cushion formation from which the non-coronary leaflet arises [18][19][20]. These studies have indicated that the distribution of second heart field derived cells is affected in Nos3−/− and that Notch signaling plays a critical role in the formation of the intercalated cushion.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the non-facing aortic leaflet and pulmonary leaflet are considered to be derived from separately developing intercalated cushions on the posterior and anterior sides of the OFT, respectively ( Kramer, 1942 ; Lin et al, 2012 ). Although the development of the septal and parietal cushion has been studied intensively, the role of these intercalated cushions during development remains a challenging concept despite recent progress ( Anderson et al, 2003 ; Lin et al, 2012 ; Eley et al, 2018 ; Mifflin et al, 2018 ). For clarity of description of the valve leaflets and the correlation with the terminology used for the aortic leaflets in human patients with BAV, we will refer to the aortic leaflets as right coronary (RC), left coronary (LC) and non-coronary (NC) leaflets ( Sievers and Schmidtke, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that the aorta and aortic valve are developmentally related. Neural crest ( Waldo et al, 1998 ; Jiang et al, 2000 ), endothelial ( Eisenberg and Markwald, 1995 ; Kisanuki et al, 2001 ), epicardial cell lineages ( Gittenberger-de Groot et al, 2012 ) and second heart field (SHF) ( Zaffran and Kelly, 2012 )-derived cells contribute to both the ascending aorta, the aortic valve ( Eley et al, 2018 ; Mifflin et al, 2018 ) and the various components of the aortic root (valvular leaflets, annulus, sinuses of Valsalva) ( de la Cruz et al, 1977 ; Kirby et al, 1983 ; Waldo et al, 2001 ). Mouse models of BAVs show cushion formation to be an essential process during valve formation, and defects in the contributing cell lineages are known to result in BAVs ( Biben et al, 2000 ; Lee et al, 2000 ; Macatee, 2003 ; Laforest and Nemer, 2011 ; Makki and Capecchi, 2012 ; Thomas et al, 2012 ; Mommersteeg et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%